A method of vulnerability assessment for power communication network based on mechanical model - Yaosheng WANG; Yingmin ZHANG; Chang WANG (Dianxin kexue)
In order to reasonably evaluate the vulnerability of the power communication network link, a vulnerability assessment method based on the mechanical model was proposed. The bandwidth capacity occupied by the traffic on the link and the number of inter-node services were collectively referred to as nodes. The correlation between the links and the degree of correlation between the link services was regarded as an associated generalized business force. In the process of business statistics, the maximum likelihood estimation of the time-slotted time slot was adopted, and the parameters of the service were estimated by using the Poisson process as a statistical background. The number of services between links and the occupied bandwidth were regarded as work of generalized service. The logical distance of the links between nodes was obtained by the gravitational formula, and the vulnerability of the communication network was measured by the interval of logical distance. Finally, MATLAB was used to establish a model for simulation calculation, it is verified that the method can analyze and evaluate the vulnerability of the service link of the power communication network in real time and accurately.